Study of Performance and Emissions of C.I. Engine With Pongamia Based Biodiesel - Prasad, V. Sitaram (Thapar University, Patiala, 2016)
Biodiesel, an alternative fuel is derived from the fats of animals and plants. As energy demands increase and fossil fuels are limited, research is directed towards alternative renewable fuels. The main advantages of using this alternative fuel are its renewability, biodegradability and better quality of exhaust gases. It is a technically competitive and environmentally friendly alternative to conventional petro diesel fuel for use in CI engines. The use of biodiesel reduces the dependence on imported fossil fuels which continue to decrease in availability and affordability. Vegetable oils for biodiesel production vary considerably with location according to climate and feedstock availability. Generally the most abundant vegetable oil in a particular region is used as the most common feedstock. Nowadays, most of the commercial biodiesel comes from the transesterification of vegetable oil using a basic catalyst such as NaOH or KOH, because a basic catalyst acts faster than an acidic catalyst. Fuel of bio-origin is generally biodiesel obtained from edible or non-edible vegetable oil through the transesterification process. Most of the properties of biodiesel compare favorably with the characteristics required for the CI fuel. Due to the relatively high costs of edible oils, the cost of producing methyl or ethyl esters from edible oils is currently more expensive than hydrocarbon based diesel fuels. The cost of biodiesel can be reduced if we can consider non-edible oils instead of edible oils. Non-edible oils from plants such as Pongamia, hemp and neem are easily available in many parts of the world and are less expensive, as compared to edible oils. Furthermore, the use of non-edible vegetable oils is of significance because of great need for edible oil as food and they are too expensive to be used as fuels. The experimental work presented in this thesis is mainly divided into three main parts. In the first part, transesterification process is used to prepare methyl ester from non-edible oil and testing of fuel properties of selected non-edible oil and it’s methyl ester. The present work discusses the feasibility of transesterification of Pongamia oil, from the point of view of the process technology and its use in diesel engines. The influence of process variables on product yield of the transesterification process has also been studied. A lot of research has already been carried out on Jatropha oil but not on Pongamia oil. Noting this, it was decided to carry out research on Pongamia oil along with it’s methyl ester. The study of non-edible vegetable oil with and without catalyst has not yet been presented. Firstly, the optimum transesterification reaction conditions for non-edible oil with respective to different parameters were investigated. A study was conducted to standardize the esterification process parameters for the production of methyl ester of filtered Pongamia oil. The transesterification reaction is affected by molar ratio of glycerides to alcohol, catalyst, reaction temperature, reaction time, preheating time, free fatty acid and water content of oils or fats. The effect of molar ratio 4:1, 6:1 and 8:1 on ester yield and its quality were investigated. The methanolysis of non-edible oils at 60oC with 1-3% KOH were studied. The effect of process parameters such as molar ratio, catalyst concentration and reaction time was studied. This information helps standardize the esterification process for estimating the highest recovery of ester with lowest possible viscosity as well as to keep the process simple. In this thesis, an attempt has been made to review the work done on biodiesel production. In the second part, an evaluation of the engine performance of given non-edible oil, methyl ester and its 20% blends and formulation of the engine exhaust emission of given non-edible oil, methyl ester and its 20% blends has been done. In this present research work, Pongamia biodiesel and biodiesel-diesel fuel blends as alternative fuels for diesel engines were studied. An experimental investigation has been carried out to evaluate the performance and emission characteristics of a diesel engine fueled with Pongamia biodiesel and its blends (20%, 40%, 60%, 80% and 100%). The performance parameters analyzed include thermal efficiency, brake specific fuel consumption, brake specific energy consumption, and exhaust gas temperature. The exhaust emissions include oxides of nitrogen, HC, smoke, CO2, CO and oxygen level. The results of the experiment in each case were compared with baseline data of diesel fuel. Significant improvements have been observed in the performance parameters of the engine as well as exhaust emissions. The Pongamia biodiesel and biodiesel-diesel fuel blends were tested in a single cylinder direct injection diesel engine. Engine performance and exhaust emission were measured at part and full load condition. This paper investigates the scope of utilizing non edible oil (Pongamia oil) as an alternative diesel fuel. An experimental investigation has been carried out to evaluate the performance and emission characteristics of a compression ignition engine fueled with Pongamia oil and important fuel properties have been determined. It concluded that lower blends of Pongamia biodiesel (PME20) act as best alternative fuel among all tested fuel at full load condition. The objective of the present research was to explore technical feasibility of Pongamia oil in direct injection CI engine without any substantial hardware modifications. The third part, analyzes the cost assessment of given methyl esters as compared to diesel fuel and compares the tested biodiesel or methyl esters to other biodiesels such as Jatropha methyl ester, Mahua methyl ester in relation with prominent fuel properties. The objective of the present study is to reveal the effect of different fuel and its blends on the performance and emission of C. I. engine and also to show the comparative study of different fuels with diesel. A study was undertaken to examine the yield of biodiesel of high quality, fuel characterization and C.I engine performance and emission characteristics. Performance and emission in existing engines, environmental considerations and economic aspects have been studied. The different fuels and its blends were then subjected to engine performance and emission tested and compared with diesel. The economics of PME is more promising with integrated approach. The present work establishes the feasibility of biodiesel-fueled CI engine utility system for agricultural and field applications. It experimentally demonstrates that a biodiesel fueled compression ignition engine, apart from its implantation potential can contribute significantly to the twin problem of diesel oil scarcity and environmental pollution. Therefore various blends of PME, and PO can be readily adopted as a substitute fuel to the existing compression ignition engine.
Keywords: Biodiesel; Pongamia; CI Engines